Ag modified g-C3N4 composite entrapped PES UF membrane with visible-light-driven photocatalytic antifouling performance. Issue 68 (5th September 2017) - Zhang, Manying; Liu, Ziya; Gao, Yong; Shu, Li
Abstract : Membrane fouling is still the main obstacle for the wider application of membrane processes. Abstract : Membrane fouling is still the main obstacle for the wider application of membrane processes. In this study, different amounts of silver modified graphitic carbon nitride (Ag/g-C3 N4 ) were firstly introduced into polyethersulfone (PES) membranes by blending via a phase-inversion method. The impacts of Ag/g-C3 N4 addition on the membrane morphology, filtration and photocatalysis antifouling properties of Ag/g-C3 N4 /PES nanocomposite membranes were systematically studied. The results illustrated that the addition of Ag/g-C3 N4 could make the finger-like voids in Ag/g-C3 N4 nanocomposite membrane longer and wider, increasing the hydrophilicity and filtration property of the nanocomposite membrane. Also the addition of Ag/g-C3 N4 nanosheets could endow the nanocomposite membranes with excellent antibacterial, photocatalytic dye degradation and antifouling properties under visible light irradiation.